Nanocrystalline toughened titanium-based amorphous composite material and preparation process thereof
The size of the crystal toughened phase in the titanium-based amorphous composite is regulated through vacuum copper mold suction casting and high-pressure torsion processes, and the evolution of micron dendrites to nanoscale is achieved, solving the problem of uneven deformation of titanium-based amorphous composite in the loading state, and improving its work hardening ability and nanoindentation hardness.
Patent Information
- Application Number
- CN202510297143.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-13
AI Technical Summary
Titanium-based amorphous composite material exhibits uneven deformation under loading state, resulting in processing softening, limiting its widespread use in engineering applications.
The vacuum copper mold suction casting process and high-pressure torsion process are adopted to regulate the size of the crystal toughened phase in the titanium-based amorphous composite material through large plastic deformation method, and the evolution of micron dendrites to nanoscale is achieved.
By forming nanocrystals of 20-300nm, the nanoindentation hardness and uniform plastic deformation strain of the titanium-based amorphous composite material are improved, and its work hardening ability is improved, and localized shear softening of the amorphous matrix is avoided.
Smart Images

Figure CN119776749A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, in particular to a nanocrystalline toughened titanium-based amorphous composite material and a preparation process thereof. Background Art
[0002] Amorphous composite materials have great application demands in the fields of aviation industry, precision instrument parts, mobile phone industry, etc. due to their excellent mechanical properties such as high strength, high toughness, excellent corrosion resistance and large elastic limit. Among them, the addition of crystal toughening phase is an important factor in realizing the plastic deformation ability of amorphous alloys. Therefore, the regulation of crystal toughening phase is one of the key technologies restricting the development and application of amorphous composite materials. Titanium-based amorphous composite materials consist of two parts: amorphous matrix and crystal toughening phase. The plastic deformation carrier of the amorphous matrix is a highly localized shear band, which causes the amorphous matrix to show brittle failure. The addition of crystal toughening phase can effectively prevent the expansion of localized shear bands and improve the plastic deformation ability of amorphous composite materials. However, because the work hardening ability of the crystal phase during deformation is difficult to surpass the shear softening of the amorphous matrix, most titanium-based amorphous composite materials show uneven deformation under loading, that is, work softening. This phenomenon is another stumbling block restricting the application of titanium-based amorphous composite materials in engineering.
[0003] According to the current public research, laser additive manufacturing, composition control and other methods can be used to control the size and distribution of the crystal phase in titanium-based amorphous composite materials, thereby improving the plastic deformation capacity of the composite materials. However, in terms of preparation technology and raw material ratio, the morphology and distribution of the crystal phase in titanium-based amorphous composite materials are at a disadvantage in terms of operation methods and cost control, and require a lot of experimental verification, which takes a long time. Summary of the invention
[0004] The main purpose of the present invention is to propose a nanocrystalline toughened titanium-based amorphous composite material and its preparation process, to achieve the regulation of the size of the crystal toughening phase in the titanium-based amorphous composite material through a large plastic deformation method, and then to improve the performance of the titanium-based amorphous composite material.
[0005] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions: A preparation process of a nanocrystalline toughened titanium-based amorphous composite material comprises the following steps: S1. Preparing titanium-based amorphous composite materials by vacuum copper mold suction casting process; S2. Take a cylindrical sample from the titanium-based amorphous composite material and perform high-pressure torsion to obtain a nanocrystal-toughened titanium-based amorphous composite material.
[0006] As a preferred solution of the preparation process of a nanocrystalline toughened titanium-based amorphous composite material described in the present invention, wherein: in the step S1, the titanium-based amorphous composite material, in atomic percentage, includes: Ti 41%, Zr 32%, Ni 6%, Ta7%, Be 14%.
[0007] As a preferred solution of the preparation process of a nanocrystalline toughened titanium-based amorphous composite material described in the present invention, wherein: in the step S1, the mold of the vacuum copper mold suction casting process is a cylindrical mold with a diameter of 6 mm and a length of 80 mm.
[0008] As a preferred solution of the preparation process of the nanocrystalline toughened titanium-based amorphous composite material described in the present invention, wherein: in the step S2, the cylindrical sample is a cylindrical sample with a diameter of 6 mm and a height of 3 mm.
[0009] As a preferred solution of the preparation process of a nanocrystalline toughened titanium-based amorphous composite material described in the present invention, wherein: in the step S2, the pressure of the high-pressure torsion is 3-5GPa, the number of revolutions is 30-50r, and the high-pressure torsion is carried out at room temperature.
[0010] As a preferred solution of the preparation process of the nanocrystalline toughened titanium-based amorphous composite material described in the present invention, wherein: in the step S2, the dimensional deformation of the high-pressure torsion specimen along the height direction is ≥50%.
[0011] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution: A nanocrystal-toughened titanium-based amorphous composite material is prepared by adopting the above-mentioned preparation process of the nanocrystal-toughened titanium-based amorphous composite material.
[0012] As a preferred embodiment of the nanocrystal-toughened titanium-based amorphous composite material described in the present invention, the nanocrystals of the titanium-based amorphous composite material are β-Ti with a BCC structure, and the nanocrystals are in the form of stretched dendrites or agglomerated particles with a size of 20-300 nm.
[0013] The beneficial effects of the present invention are as follows: The present invention proposes a nanocrystal toughened titanium-based amorphous composite material and a preparation process thereof, which adopts a copper mold suction casting method + high-pressure torsion process, and controls the morphology and size of dendrites in the composite material by a large plastic deformation method, so as to achieve the evolution of micron-level dendrites in the composite material to nano-level, thereby obtaining a nanocrystal toughened titanium-based amorphous composite material, wherein the size of the nanocrystal is 20-300nm, the nanoindentation hardness is ≥4.05GPa, and the uniform plastic deformation strain is ≥4%. The formation of nanocrystals avoids the softening caused by highly localized shear in the amorphous matrix, and improves the work hardening ability of the titanium-based amorphous composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0015] Figure 1 This is a microstructure diagram of the titanium-based amorphous composite material according to Example 1 of the present invention; Figure 2 This is a microstructure diagram of the titanium-based amorphous composite material of Comparative Example 1 of the present invention.
[0016] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0017] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The present invention provides a nanocrystal-toughened titanium-based amorphous composite material and a preparation process thereof, wherein the shape and size of the crystal toughening phase are regulated, a copper mold suction casting method + high-pressure torsion process is adopted, and the morphology and size of dendrites in the composite material are regulated by a large plastic deformation method, so that the evolution of micron-level dendrites in the composite material to nano-level is achieved, thereby obtaining a nanocrystal-toughened titanium-based amorphous composite material, wherein the size of the nanocrystal is 20-300nm, the nanoindentation hardness is ≥4.05GPa, and the uniform plastic deformation strain is ≥4%. The defects of strain softening and hardness reduction caused by highly localized shearing of the amorphous matrix in the titanium-based amorphous composite material are solved, and the performance of the titanium-based amorphous composite material is improved.
[0019] According to one aspect of the present invention, the present invention provides the following technical solution: A preparation process of a nanocrystalline toughened titanium-based amorphous composite material comprises the following steps: S1. Preparing titanium-based amorphous composite materials by vacuum copper mold suction casting process; S2. Take a cylindrical sample from the titanium-based amorphous composite material and perform high-pressure torsion to obtain a nanocrystal-toughened titanium-based amorphous composite material.
[0020] Preferably, in step S1, the titanium-based amorphous composite material includes, in atomic percentage, 41% Ti, 32% Zr, 6% Ni, 7% Ta, and 14% Be.
[0021] Preferably, in step S1, the base alloy is melted in a vacuum state, and a cylindrical alloy is obtained by suction casting; the mold of the vacuum copper mold suction casting process is a cylindrical mold with a diameter of 6 mm and a length of 80 mm.
[0022] Preferably, in step S2, the cylindrical sample is a cylindrical sample with a diameter of 6 mm and a height of 3 mm.
[0023] Preferably, in step S2, the pressure of high-pressure torsion is 3-5GPa, the number of revolutions is 30-50r, and the high-pressure torsion is performed at room temperature. Specifically, the pressure of high-pressure torsion can be, for example, any one of 3GPa, 4GPa, 5GPa or a range between any two thereof; the number of revolutions can be, for example, any one of 30r, 40r, 50r or a range between any two thereof. The formation of nanocrystals is closely related to the large plastic deformation caused by high-pressure torsion. There are two nano-crystalization phenomena in the plastic deformation process: one is that the micron-sized dendrites are stretched and separated due to torsion, and the size gradually decreases to the nanoscale; the other is that agglomerated particle nanocrystals appear inside the dendrites due to the torsion pressure and the strong interaction with the amorphous matrix.
[0024] Preferably, in step S2, the dimensional deformation of the high-pressure torsion specimen along the height direction is ≥50%. The dimensional deformation of the high-pressure torsion specimen along the height direction is related to the torsion pressure and the number of turns in the high-pressure torsion process, and the dimensional deformation of the high-pressure torsion specimen along the height direction is preferably 50-75%; specifically, the deformation of the specimen after high-pressure torsion deformation can be, for example, any one of 50%, 55%, 60%, 65%, 70%, 75%, or a range between any two of them.
[0025] According to another aspect of the present invention, the present invention provides the following technical solution: A nanocrystal toughened titanium-based amorphous composite material is prepared by the above-mentioned nanocrystal toughened titanium-based amorphous composite material preparation process, wherein the nanocrystal is β-Ti with a BCC structure, the nanocrystal is in a dendrite stretching shape or agglomerated particle shape, and the size is 20-300nm.
[0026] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.
[0027] A vacuum melting furnace was used to prepare titanium-based amorphous composite cast specimens by copper mold suction casting. The mold for the vacuum copper mold suction casting process was a cylindrical mold with a diameter of 6 mm and a length of 80 mm. A cylindrical specimen of 6 mm (diameter) × 3 mm (height) was cut from the cast specimen as a high-pressure torsion specimen for later use.
[0028] Table 1 Detection composition of titanium-based amorphous composite materials (at.%)
[0029] Example 1 A preparation process of a nanocrystalline toughened titanium-based amorphous composite material comprises the following steps: S1. Preparing titanium-based amorphous composite materials by vacuum copper mold suction casting process; S2. Take a cylindrical sample from the titanium-based amorphous composite material and conduct a high-pressure torsion test. The pressure of the high-pressure torsion is controlled to be 5 GPa, the number of revolutions is 50 r (H-50), and the test is carried out at room temperature; In Example 1, the height of the sample after deformation becomes 0.75 mm, and the deformation amount is (3-0.75) / 3=75%; its microstructure morphology is shown in Figure 1 As shown ( Figure 1 The upper left side of the figure is a TEM image, the lower left side is a SAED image, and the right side is a SEM image). It can be seen that the micron-sized dendrites are deformed by high-pressure torsion, and severe plastic deformation occurs inside the dendrites and at the positions subjected to torsion and stretching, forming nanocrystals (such as the area indicated by the arrow in the SEM image). The size of the nanocrystals is 20-150nm. The size of the crystalline phase in the titanium-based amorphous composite material is controlled by the process of high-pressure torsion to refine the size and evolve into nano-scale crystals; the nanoindentation hardness of the cast sample of the titanium-based amorphous composite material is 4.03GPa, the nanoindentation hardness of the H-50 sample is 4.47GPa, and the uniform plastic deformation strain is 4%.
[0030] Example 2 A preparation process of a nanocrystalline toughened titanium-based amorphous composite material comprises the following steps: S1. Preparing titanium-based amorphous composite materials by vacuum copper mold suction casting process; S2. Take a cylindrical sample from the titanium-based amorphous composite material and conduct a high-pressure torsion test. The pressure of the high-pressure torsion is controlled to be 5 GPa, the number of revolutions is 30r (H-30), and the test is carried out at room temperature; In Example 2, the height of the deformed sample becomes 1.38 mm, and the deformation amount is (3-1.38) / 3=54%; the size of the nanoscale crystal is 50-300 nm, and the size of the crystal phase in the titanium-based amorphous composite material is controlled by high-pressure torsion process means to refine the size and evolve into nanoscale crystals; the nanoindentation hardness of the cast sample of the titanium-based amorphous composite material is 4.03 GPa, the nanoindentation hardness of the H-30 sample is 4.05 GPa, and the uniform plastic deformation strain is 5%.
[0031] Comparative Example 1 The difference from Embodiment 1 is that step S2 is not performed.
[0032] In this comparative example, a titanium-based amorphous composite material was prepared by vacuum copper mold suction casting. Figure 2 The microstructure diagram of the titanium-based amorphous composite material in Comparative Example 1, wherein the size of the dendritic β-Ti crystal toughening phase is 1-2 μm. The nanohardness of the titanium-based amorphous composite material is 4.03 GPa, and the uniform plastic deformation strain is 2%.
[0033] Comparative Example 2 The difference from the first embodiment is that the number of revolutions of the high-voltage twist in step S2 is controlled to be 10r (H-10).
[0034] The nanocrystal size in the H-10 sample in Comparative Example 2 is 350-400 nm, which is larger than the nanocrystal size described in Examples 1 and 2, which is due to insufficient deformation. The height of the sample after deformation in Comparative Example 2 becomes 2 mm, the deformation is (3-2) / 3=33.3%, the nanohardness is 4.02 GPa, and the uniform plastic deformation is 2.3%.
[0035] It can be seen from the above embodiments and comparative examples that the present invention adopts a copper mold suction casting method + high-pressure torsion process, and regulates the morphology and size of dendrites in the composite material by a large plastic deformation method, thereby realizing the evolution of micron-scale dendrites in the composite material to nanoscale, thereby obtaining a nanocrystal-toughened titanium-based amorphous composite material, wherein the size of the nanocrystal is 20-300nm, the nanoindentation hardness is ≥4.05GPa, and the uniform plastic deformation strain is ≥4%.
[0036] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A process for preparing a nanocrystalline toughened titanium-based amorphous composite material, characterized in that: The steps include: S1. Preparing titanium-based amorphous composite materials by vacuum copper mold suction casting process; S2. Take a cylindrical sample from the titanium-based amorphous composite material and perform high-pressure torsion to obtain a nanocrystal-toughened titanium-based amorphous composite material.
2. The process for preparing the nanocrystalline toughened titanium-based amorphous composite material according to claim 1, characterized in that: In the step S1, the titanium-based amorphous composite material includes, in atomic percentage, 41% Ti, 32% Zr, 6% Ni, 7% Ta, and 14% Be.
3. The process for preparing the nanocrystalline toughened titanium-based amorphous composite material according to claim 1, characterized in that: In the step S1, the mold for the vacuum copper mold suction casting process is a cylindrical mold with a diameter of 6 mm and a length of 80 mm.
4. The process for preparing the nanocrystalline toughened titanium-based amorphous composite material according to claim 1, characterized in that: In step S2, the cylindrical sample is a cylindrical sample with a diameter of 6 mm and a height of 3 mm.
5. The process for preparing the nanocrystalline toughened titanium-based amorphous composite material according to claim 1, characterized in that: In the step S2, the pressure of the high-pressure twisting is 3-5 GPa, the number of revolutions is 30-50 r, and the high-pressure twisting is performed at room temperature.
6. The process for preparing the nanocrystalline toughened titanium-based amorphous composite material according to claim 1, characterized in that: In the step S2, the dimensional deformation of the high-pressure torsion test specimen along the height direction is ≥50%.
7. A nanocrystal-toughened titanium-based amorphous composite material, characterized in that: The nanocrystalline toughened titanium-based amorphous composite material is prepared by the preparation process of any one of claims 1 to 6.
8. The nanocrystalline toughened titanium-based amorphous composite material according to claim 7, characterized in that: The nanocrystals of the titanium-based amorphous composite material are β-Ti with a BCC structure, and the nanocrystals are in the form of stretched dendrites or agglomerated particles, with a size of 20-300 nm.
9. The nanocrystalline toughened titanium-based amorphous composite material according to claim 7, characterized in that: The nanoindentation hardness of the nanocrystal-toughened titanium-based amorphous composite material is ≥4.05 GPa, and the uniform plastic deformation strain is ≥4%.
Citation Information
Patent Citations
Method for preparing amorphous / nano-crystalline nickel titanium shape memory alloy by local-sheath severe plastic deformation
CN102383080A
Titanium-based porous sintering composite material with nanocrystal tissues and preparation method thereof
CN103572088A
Endogenous-phase titanium-based amorphous composite material with improved strength and plasticity and preparation method thereof
CN104264081A
Method for improving Fe-based amorphous alloy water electrolysis hydrogen evolution catalytic activity through plastic deformation treatment
CN111139346A
Manufacturing Method for Zirconium Alloy Tubular Products
US20220314289A1